Proceedings of the 6th International Conference on Human-Agent Interaction 2018
DOI: 10.1145/3284432.3284433
|View full text |Cite
|
Sign up to set email alerts
|

Using a Robot Peer to Encourage the Production of Spatial Concepts in a Second Language

Abstract: We conducted a study with 25 children to investigate the efectiveness of a robot measuring and encouraging production of spatial concepts in a second language compared to a human experimenter. Productive vocabulary is often not measured in second language learning, due to the diiculty of both learning and assessing productive learning gains. We hypothesized that a robot peer may help assessing productive vocabulary. Previous studies on foreign language learning have found that robots can help to reduce languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…vocabulary test and storytelling contexts (e.g., Kory and Breazeal, 2014;Kory Westlund et al, 2017b;Wallbridge et al, 2018). The present study suggests that the robot's entrainment may influence expressive ability.…”
Section: Learningmentioning
confidence: 56%
See 1 more Smart Citation
“…vocabulary test and storytelling contexts (e.g., Kory and Breazeal, 2014;Kory Westlund et al, 2017b;Wallbridge et al, 2018). The present study suggests that the robot's entrainment may influence expressive ability.…”
Section: Learningmentioning
confidence: 56%
“…This suggests that perhaps entrainment did not affect children's mirroring of the words the robot used so much as their expressive ability to use the key words present in the story. Prior work has shown that social robots can be successful at prompting children to demonstrate expressive vocabulary skills in both vocabulary test and storytelling contexts (e.g., Kory and Breazeal, 2014 ; Kory Westlund et al, 2017b ; Wallbridge et al, 2018 ). The present study suggests that the robot's entrainment may influence expressive ability.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of Human-Robot Interaction, we typically run experiments to see how human participants react to robots in some way [Hoffman and Zhao 2020]. For instance, this might involve exploring how certain robot behaviours affect people's perceptions of that robot [Johanson et al 2019;Winkle et al 2021], or whether robots can facilitate learning of a second language [Vogt et al 2019;Wallbridge et al 2018], or even how children play with them [Boccanfuso et al 2016]. However, unlike (most) robots, people can be highly unpredictable.…”
Section: Introductionmentioning
confidence: 99%